IMPLEMENTATION OF ING MADYA MANGUN KARSA IN SMES IN YOGYAKARTA, INDONESIA AND COMMUNITY LEARNING CENTER IN SABAH, MALAYSIA - Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna; Nisa, Ana Fitrotun; Wahidah, Umi; Lada, Suddin Bin (Yayasan Education and Social Center, 2024)
This community service aims to explain the application of ing madya mangun karsa from Ki Hajar Dewantara's leadership trilogy to SMEs in Yogyakarta consisting of UMKM Pottery & Ceramic Crafts